(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to determine the food composition of the bee-eater genus - Merops (European Bee-eater -Merops apiasterand Blue-cheeked Bee-eater -Merops persicus) found in Uzbekistan, as well as the mass of their stomachs.Determining the composition of food and their seasonal variability makes it possible to assess the natural and economic importance of these species.The variability in the mass of the stomach of the studied birds is explained by the processes of hyperphagia and lipogenesis occurring during the period of pre-preparation for autumn migration.